Vascular access and clinical competency: Which elements matter? The development of three bottom-up and evidence-grounded self-assessment tools. Issue 2 (March 2023) - Rigo, Carla; Grazioli, Marco; Caravella, Giuseppe; Ursino, Francesco; Zerla, Pietro; Magon, Arianna; Dellafiore, Federica; Caruso, Rosario
Background: Assessing competency in the speciality of vascular access is still limited, and few valid and reliable tools are available. Therefore, this study aimed to develop and validate three different tools for assessing competency in managing the care of short peripheral cannulas (SPCs), midlines, peripherally inserted central catheters (PICCs), centrally inserted central catheters (CICCs), and arterial catheters (ACs) (tool one), placing SPCs (tool two), placing PICCs and midlines (tool three). Methods: A two-phase and multi-method design was adopted. Phase one was implemented to develop the initial pool of items for each tool, starting from a literature overview. Panel discussions were adopted for developing the items. In phase two, the developed items were tested for content and face validity, involving a panel of 10 experts. Once obtained adequate content validity, a cross-sectional data collection was implemented to enroll three samples of healthcare workers who had to assess their competency through the developed tools. Dimensionality was assessed by performing a principal component analysis (PCA) and assessing internal consistency (Cronbach's α). Results: Tool one had 26 items, and the dimensionality was given by placement, risk assessment, procedure conformity and traceability, and patient education to self-care. Tool two had 35 items; its principal components were: risk evaluation, identification, clinical assessment and orientation to self-care, placement, and procedure registration shaped the competency of placing SPCs. Tool three had 31 items; its principal components were: risk assessment, placement, conformity to standards and procedure traceability, education, and orientation to self-care were the essential elements for adequately placing midlines and PICCs. Cronbach's α values ranged between 0.806 and 0.959. Conclusions: The three developed tools reflected the core elements of competency in each application area, representing an initial framework that could be useful in future research and educational projects. Cross-national investigations are required to corroborate the described results.